Profiling microRNAs through development of the parasitic nematode Haemonchus identifies nematode-specific miRNAs that suppress larval development - Marks, Neil D; Winter, Alan D; Gu, Henry Y; Maitland, Kirsty; Gillan, Victoria; Ambroz, Martin; Martinelli, Axel; Laing, Roz; MacLellan, Rachel; Towne, Jessica; Roberts, Brett; Hanks, Eve; et al. (Scientific reports, 2019)
Parasitic nematodes transition between dramatically different free-living and parasitic stages, with correctly timed development and migration crucial to successful completion of their lifecycle. However little is known of the mechanisms controlling these transitions. microRNAs (miRNAs) negatively regulate gene expression post-transcriptionally and regulate development of diverse organisms. Here we used microarrays to determine the expression profile of miRNAs through development and in gut tissue of the pathogenic nematode Haemonchus contortus. Two miRNAs, mir-228 and mir-235, were enriched in infective L3 larvae, an arrested stage analogous to Caenorhabditis elegans dauer larvae. We hypothesized that these miRNAs may suppress development and maintain arrest. Consistent with this, inhibitors of these miRNAs promoted H. contortus development from L3 to L4 stage, while genetic deletion of C. elegans homologous miRNAs reduced dauer arrest. Epistasis studies with C. elegans daf-2 mutants showed that mir-228 and mir-235 synergise with FOXO transcription factor DAF-16 in the insulin signaling pathway. Target prediction suggests that these miRNAs suppress metabolic and transcription factor activity required for development. Our results provide novel insight into the expression and functions of specific miRNAs in regulating nematode development and identify miRNAs and their target genes as potential therapeutic targets to limit parasite survival within the host.
Keywords: Receptor, Insulin; Caenorhabditis elegans; druhová specificita; RNA, Messenger; Male; MicroRNAs; vývojová regulace genové exprese; mikro RNA; Gene Expression Regulation, Developmental; RNA helmintů; mužské pohlaví; RNA, Helminth; Gene Deletion; Species Specificity; Cholestenes; receptor inzulinu; Caenorhabditis elegans Proteins; larva; Animals; ženské pohlaví; proteiny Caenorhabditis elegans; zvířata; delece genu; Larva; cholesteny; genová ontologie; Female; Gene Ontology; Haemonchus; messenger RNA